Addressing School Bullying in Malaysia: Doctrinal Gaps, Legal Accountability, and Reform Imperatives - Zulazhar Tahir; Jal Zabdi Mohd Yusoff; Siti Zaharah Jamaluddin (Sriwijaya Law Review, 2026)
Education plays a central role in Malaysia’s aspiration to attain developed nation status, with schools functioning not only as institutions of learning but also as environments responsible for students’ physical, emotional, and psychological safety. In recent years, bullying has emerged as a serious and growing concern within Malaysian schools, reflecting a global trend. National statistics show an increase in reported bullying cases between 2021 and 2023, underscoring the urgency of effective legal and institutional responses. While not all incidents result in physical harm or death, bullying often causes significant psychological trauma, adversely affecting students’ mental health, academic performance, and long-term well-being. Perpetrators, in turn, may face disciplinary and legal consequences. From a legal standpoint, school bullying in Malaysia is addressed indirectly through a fragmented framework comprising criminal law, tort principles, child protection legislation, and internal school disciplinary mechanisms. This lack of a dedicated legal framework has created uncertainty regarding the respective duties and liabilities of schools, teachers, parents, and students, resulting in inconsistent enforcement and remedies. This article employs qualitative legal research methods, drawing on library research and content analysis of statutes, reported cases, academic literature, and parliamentary debates. It evaluates the effectiveness of the existing legal approach and doctrinally synthesises relevant pre-2025 case law. The study also adopts a comparative perspective by examining legal approaches in the United Kingdom, India, and Singapore. The findings reveal significant legal gaps and inconsistencies that undermine victim protection and effective intervention. Accordingly, the article advocates a more holistic and coherent legal framework to address school bullying within Malaysia’s education system.